Dietary habits and physical activity patterns among Slovenian elderly: cross-sectional survey with cluster analysis - Joca Zurc; Cirila Hlastan-Ribič; Brigita Skela-Savič (Nurses and Midwives Association of Slovenia, 2015)
Introduction: Physical activity and a healthy diet are significant predictors of healthy ageing-they help the elderly maintain their physical and mental health, and prevent chronic diseases. Methods: The data for the empirical quantitative survey were collected on the sample of 218 elderly community-dwelling participants (aged 65 years or more), using a structured questionnaire for self-reporting. Data analyses were proceed with the bivariate statistics, and multivariate hierarchical cluster analysis. Results: Most respondents reported good dietary habits (83.1%) and a satisfactory physical activity level (60.5%). On average, the elderly eat 3-4 meals per day (59.8%) and engage in physical activity at least three times a week (58.6%), with interventions lasting 15 minutes or more (84.4 %) and non-organized activity prevailing (96.2%). Ward's method yielded three clusters with homogenous dietary and physical activity patterns: 'Health Conscious' (30.8%), 'At Risk' (42.7%) and 'Special Requirements' (26.5%). Significant differences were identified between clusters and educational level (p = 0.001). Discussion and conclusions: In the future, special attention should be placed on the elderly group with a lower educational level and special dietary and physical activity requirements. Additional studies on representative samples are required for a comprehensive investigation into the lifestyle behaviours of elderly individuals.